Spatial and Temporal Variations of Heavy Metals’ Bioavailability in Soils Regulated by a Combined Material of Calcium Sulfate and Ferric Oxide - Chi Zhang; Jie Li; Yuxia Dai; Williamson Gustave; Weiwei Zhai; Zhong Zhong; Jianmeng Chen (Toxics, 2023)
Heavy metal pollution in soils threatens food safety and human health. Calcium sulfate and ferric oxide are commonly used to immobilize heavy metals in soils. However, the spatial and temporal variations of the heavy metals’ bioavailability in soils regulated by a combined material of calcium sulfate and ferric oxide (CSF) remain unclear. In this work, two soil column experiments were conducted to investigate the spatial and temporal variations of CSF immobilized Cd, Pb, and As. In the horizontal soil column, the results showed that CSF’s immobilization range for Cd increased over time, and adding CSF in the center of the soil column decreased the concentrations of bioavailable Cd significantly, up to 8 cm away by day 100. The CSF immobilization effect on Pb and As only existed in the center of the soil column. The CSF’s immobilization depths for Cd and Pb in the vertical soil column increased over time and extended to 20 cm deep by day 100. However, the CSF’s immobilization depths for As only extended to between 5 and 10 cm deep after 100 days of incubation. Overall, the results from this study can serve as a guide to determine the CSF application frequency and spacing distance for the in-situ immobilization of heavy metals in soils.